PENGARUH FASILITAS, LOKASI, DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN HOTEL NIWA CANTING SEMARANG DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Irene Nathalia Setiawan; Scorina Dwiantari; Bambang Heriawan (JURNAL ILMIAH EDUNOMIKA, 2024)
One of the important things that every company needs to do and pay attention to is retaining existing customers and continuing to work on new potential customers so that customers don't leave the company and become customers of other companies. Loyal customers are an opportunity to get new customers. Apart from satisfaction, facilities also play a role in attracting consumers. Facilities are also very important in increasing consumer loyalty. Good facilities can make consumers feel comfortable, but if the facilities provided are bad then consumers will feel uncomfortable and feel at a loss. Basically, the location for all factory and service businesses is important because it is directly related to the efficiency and effectiveness of the business.